Metonímias e metáforas em Terra sonâmbula de Mia Couto - Albuquerque, Antonio Rocha de (2024)
This research aimed to demonstrate how Mia Couto (2007), in her novel Terra sonâmbula, used the linguistic tools of metonymies and metaphors to iconize the extended semantic fields of her literary construction in this unique work of contemporary Mozambican literature. This is a bibliographical study, with a qualitative approach. For the analysis of metonymic and metaphorical constructions, theoretical support was sought in studies by Todorov (1981), Savioli and Fiorin (2011), Ricoeur (2000), among others. Terra somnambula inhabits the space of a sleeping land, but remains in a state of transition between sleep and wakefulness, in polyphonic and dialogic rings, in a milonga between buried lives and other living ones. With complete empirical knowledge about the reality, myths and oral narratives of the roots of Mozambique, Mia Couto (2007) divided and distinguished in Terra sonâmbula the predator (war) and the prey (Muidinga, Tuahir and Kindzu), characters who star in the novel , in all its prosaic and poetic character of a civilizing process under construction. The author uses a creative process using needles of words in a crochet of languages, uniting poles of poetic, mythical and mystical fiction aligned with reality. It is a novel of phenomenal spectrums of the art of narration, attentive to the ancestral and oral traditions of a people from a living land, in a trance. Between silence and noise, the real and the symbolic of a historical and fictional narrative field.